2022
DOI: 10.3390/ijerph19095742
|View full text |Cite
|
Sign up to set email alerts
|

Modeling di (2-ethylhexyl) Phthalate (DEHP) and Its Metabolism in a Body’s Organs and Tissues through Different Intake Pathways into Human Body

Abstract: Phthalate esters (PAEs) are ubiquitous in indoor environments as plasticizers in indoor products. Residences are often exposed to indoor PAEs in the form of gas, particles, settled dust, and surface phases. To reveal the mechanism behind the accumulation of PAEs in different tissues or organs such as the liver and the lungs when a person exposed to indoor PAEs with different phases, a whole-body physiologically based pharmacokinetic model for PAEs is employed to characterize the dynamic process of phthalates b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“…DEHP and its biometabolite MEHP are known for their toxicity to main organs, especially the reproductive system. 36 , 38 , 39 Excess ROS generation, blood-testis barrier disintegration, and steroid synthesis may be triggered by DEHP exposure, as revealed in our previous studies. 22 , 40 However, the potential mechanism of DEHP-induced spermatogenic dysfunction in puberty remains unclear.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…DEHP and its biometabolite MEHP are known for their toxicity to main organs, especially the reproductive system. 36 , 38 , 39 Excess ROS generation, blood-testis barrier disintegration, and steroid synthesis may be triggered by DEHP exposure, as revealed in our previous studies. 22 , 40 However, the potential mechanism of DEHP-induced spermatogenic dysfunction in puberty remains unclear.…”
Section: Discussionsupporting
confidence: 65%
“…MEHP, the main biometabolite of DEHP, exerts a primary toxic effect on most organs. 36 , 37 Based on our previous study, MEHP was administered in vitro . 22 Scanning electron microscopy (SEM) was used to evaluate inflammasomes in MEHP-treated cell lines ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Given the relatively heavy molecular weight phthalates with lower vapour pressures like DEHP, which has a tendency to be in dust 54 , it seems reasonable that DEHP had a dust ingestion contribution of > 90% to the indoor intake. The study by Li et al 55 indicated that dust ingestion of DEHP mainly accumulated in liver and had the greatest adverse in uence on liver compared to other humans' organs. On the other hand, low-molecular-weight phthalates such as DEP, DiBP, and DnBP tend to exist in the gas phase.…”
Section: Discussionmentioning
confidence: 99%